1985
DOI: 10.1037/h0088532
|View full text |Cite
|
Sign up to set email alerts
|

Termination anxiety as it affects the therapist.

Abstract: Writers on psychotherapeutic thought have commented on the dearth of literature on the subject of termination, especially in the anxieties and apprehension that termination may arouse in the therapist. This paper addresses the concept of termination anxiety as it affects the therapist by 1) tracing the various sources of uneasiness around the ending of therapy and 2) theorizing about the possible defense maneuvers a therapist uses in order to circumvent the anxiety. Subsequently, it considers some implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
(42 reference statements)
0
26
0
Order By: Relevance
“…This view applies more often to clients, but has also been applied to therapists, whose responses to termination, positive as well as negative, have been analyzed as features of the mourning process (Martin & Schurtman, 1985;Quintana, 1993;Ward, 1984).…”
Section: Limitations and Contributionsmentioning
confidence: 98%
See 1 more Smart Citation
“…This view applies more often to clients, but has also been applied to therapists, whose responses to termination, positive as well as negative, have been analyzed as features of the mourning process (Martin & Schurtman, 1985;Quintana, 1993;Ward, 1984).…”
Section: Limitations and Contributionsmentioning
confidence: 98%
“…Termination of treatment is recognized as an emotionally difficult experience not only for clients (Anthony & Pagano, 1998;Baum, 2005;Fortune, 1987;Fortune, Pearlingi, & Rochelle, 1992;Kramer, 1990;Marx & Gelso, 1987), but also for therapists (Martin & Schurtman, 1985;Northen, 1988;Siebold, 1991;Webb, 1985). In this paper patient and client are used interchangeably to indicate the recipient of the therapeutic services.…”
Section: Introductionmentioning
confidence: 96%
“…Most of the 1 studies exploring clients feelings stress anger, regression, rage, denial, (Bywaters, 1975;Fortune et al, 1992), as well as loss, sadness, and anxiety (Kramer, 1986). At the same time, various studies identify pride, sense of accomplishment (Fortune et al, 1992;Martin & Schurtman, 1985;Webb, 1985), sense of maturity, and feelings of newly gained independence (Fortune, 1987).…”
Section: Introductionmentioning
confidence: 94%
“…Nor has the length of the treatment (Northen, 1988). On the other hand, clients' previous loss experiences (Gould, 1977;Martin & Schurtman, 1985;Marx & Gelso, 1987;Webb, 1985) have been found to make TT more difficult.…”
Section: Introductionmentioning
confidence: 96%
“…Even if termination of therapy is an expected event, therapists may still experience negative reactions. Martin and Schurtman (1985) found that therapists often felt uneasy about the ending of therapy and experienced a variety of affective reactions. They reported that therapists experienced feelings of loss, especially if they had unresolved issues of separation in their own histories.…”
Section: The Effects Of Termination On Therapistsmentioning
confidence: 99%